Validitas Bahan Ajar LKS Menulis Naskah Drama Siswa Kelas VIII SMP se-Kabupaten Musi Rawas - Sri Murti; Muhtadin Muhtadin (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to describe the validity of teaching materials LKS writing drama scripts for eighth-grade students of Musi Rawas Regency. Teaching materials developed to increase student interest in class VIII SMP throughout Musi Rawas Regency. Researchers are also motivated to conduct this development research because they want to add learning references in writing drama scripts. Therefore, the researcher wants to develop a Student Worksheet with examples of drama scripts based on the folklore Musi Rawas. The method used is the research and development (R&D) method with the Dick & Carey model which is limited to 8 stages. Expert validation was carried out with three experts, namely design validation expert, linguistic validation expert, and content/material validation expert. The research instruments were divided into the test, questionnaire, interview, questionnaire, rating scale, and attitude scale, observation, and sociometry. Research activities in developing this teaching material model, researchers used test guideline instruments, interviews, questionnaires, and observation sheets to validate research data. The results showed that the validity of LKS teaching materials writing drama scripts for eighth-grade students of Musi Rawas Regency was included in the good category with a percentage of 79.17% originating from the results of design, language, and material validation experts. Thus, the validity of LKS teaching material writing drama scripts in this study can be accepted as correct. The LKS teaching materials developed were valid and the LKS teaching materials after being tested at school could increase the interest in learning to write drama scripts for eighth-grade students of Musi Rawas.